Enhancing Foot Sensitivity in Diabetes Mellitus Patients: The Impact of Diabetic Foot Exercises - Uba, Nuraini Achmad; Mubarrok, Alik Septian; Kurdi, Fahruddin (Jurnal Kegawatdaruratan Medis Indonesia, 2025)
Physical activity is an essential way for people with Diabetes Mellitus, especially in dealing with increased sensitivity of the foot. Diabetic foot gymnastics is an exercise performed by DM patients to prevent injuries, help smooth blood circulation, and increase foot sensitivity. The study was designed as a one-group pre and post-test design. The study was conducted on 22-26 May 2018 at the Public Health Center of Peterongan. The sample consisted of 35 respondents using the Purposive Sampling technique. The Independent variable was Diabetic foot gymnastics; the dependent variable was foot sensitivity. The results of analysis used the Wilcoxon test at significance level α = 0.05 was found that ρ <α or 0,000 <0.05, which means that there was an influence of diabetic foot gymnastics with plastic ball to the level of foot sensitivity in DM patients, in which pre-test of half respondent (54.3%) sensitivity of the foot of the ring as many as 19 respondents, and after the post-test become higher as many as respondent (42.9%) had their sensitivity of the foot of the ring as many as 15 respondents. A sensory examination of the foot was required. Because of these results, the risk of complications in the foot could be prevented as early as possible. Normal foot sensation and abnormal foot sensation were sometimes not known by people with diabetes mellitus as one of the factors of diabetic foot gymnastics.